Transcatheter aortic valve replacement by a minimalist approach: A breath of fresh air for patients with chronic obstructive pulmonary disease. Issue 4 (1st March 2017) - Caixeta, Adriano; Lemos, Pedro A.
Key Points: A minimalist approach to transcatheter aortic valve replacement in selected patients results in shorter hospitalization and may improve short‐ and long‐term survival compared to a standard approach Minimalist TAVR can be performed with less or no intensive care unit support leading to a shorter hospitalization and improved resource utilization Diligent patient selection by the heart team and thorough education of the entire care staff are the keys to success for minimalist TAVR